Implementasi Hasil Diklat Penyuluh Agama Islam Non PNS Aspek Empat Pilar Kebangsaan di Jawa Timur - Darmani (Jurnal Kewidyaiswaraan, 2019)
The purpose of this study is to find out a) the process of implamantation pancasila values ​​by non-civil servant Islamic religious instructors in East Java, b) the process of implamantationthe values ​​of the Constitution 45 by non PNS Islamic religious instructors in East Java, c) the process of implamantationvalues -value of the Unitary State of the Republic of Indonesia by non-civil servant Islamic religious instructors in East Java, and d) the process of implamantationthe values ​​of Bhineka Tunggal Ikaby non-civil servant Islamic religious instructors in East Java. The researcher used a type of qualitative research with descriptive methods. Sources of data are taken through interviews, observation and document analysis. The analysis techniques in this study are 1) data collection, 2) data reduction, 3) data presentation, and 4) conclusion. Data validation uses triangulation and extension of participation. From the analysis of research data concluded: a) the process of implamantation Pancasila values ​​is carried out in accordance with technical instructions. The implementation of Pancasila is easier to implement because the object of guidance is already accustomed to hearing the Pancasila. b) the process of implamantationthe values ​​of the 1945 Constitution is carried out in accordance with technical instructions. The implementation of the Constitution 45 is more difficult to implement because the object of guidance is heavy with the discussion of articles which are multi-interpreted. c) the process of implamantationthe values ​​of the Unitary State of the Republic of Indonesia is carried out in accordance with technical instructions. d) the process of implamantationthe values ​​of Bhineka Tunggal Ika is carried out in accordance with technical instructions. The constraints in the implementation of the four pillars include understanding different worshipers, varying ages, and limited learning media. The solution is for the instructor to coordinate with the head of the group and the leader of the Pokjaluh, namely by repetition of the material, group discussions according to age, methods that match to the characteristics of the audience and try to prepare the appropriate media.